Stereoscopic Visual Attention-Based Regional Bit Allocation Optimization for Multiview Video Coding. (29th June 2010) - Zhang Zhang, Yun Yun; Jiang Jiang, Gangyi Gangyi; Yu Yu, Mei Mei; Chen Chen, Ken Ken; Dai Dai, Qionghai Qionghai
Abstract : We propose a Stereoscopic Visual Attention- (SVA-) based regional bit allocation optimization for Multiview Video Coding (MVC) by the exploiting visual redundancies from human perceptions. We propose a novel SVA model, where multiple perceptual stimuli including depth, motion, intensity, color, and orientation contrast are utilized, to simulate the visual attention mechanisms of human visual system with stereoscopic perception. Then, a semantic region-of-interest (ROI) is extracted based on the saliency maps of SVA. Both objective and subjective evaluations of extracted ROIs indicated that the proposed SVA model based on ROI extraction scheme outperforms the schemes only using spatial or/and temporal visual attention clues. Finally, by using the extracted SVA-based ROIs, a regional bit allocation optimization scheme is presented to allocate more bits on SVA-based ROIs for high image quality and fewer bits on background regions for efficient compression purpose. Experimental results on MVC show that the proposed regional bit allocation algorithm can achieve over 20 ~ 30 % bit-rate saving while maintaining the subjective image quality. Meanwhile, the image quality of ROIs is improved by 0 .46 ~ 0 .61  dB at the cost of insensitive image quality degradation of the background image.